Analysis of Bioactive Constituents (HPLC) of Chloroform Leaf Extract from Kalanchoe pinnata in Takum, Taraba State Nigeria - Joel, Emmanuel Askebnde; Wilson, Ubur Terzulum; Umaru, Isaac John; Iseko, Kingsley Iyoko; Istifanus, Dafup Katdel; Oladele, Gloria Omonefe (Darul Yasin Al Sys, 2024)
HPLC techniques were employed to analyze the bioactive components of the chloroform leaf extract of Kalanchoe pinnata leaf from Takum in Taraba State. A botanist from Taraba State University's Department of Biological Sciences in Jalingo identified the plant leaves, which were then gathered, cleaned, and processed. Using cold maceration, extraction was done by weighing 1500g of the powdered leaf into 1 liter of ethanol and distill water, respectively. Until further investigation, the extracts were stored in a refrigerator in a firmly closed container. The injection valve was used for the HPLC analysis, and the conditions were 20 μl, a UV variable wavelength detector (set at 300 nm), reprosol 100 C8mn, 5 μm 4.6 x 150mm column (30°C), and sensitivity of 0.001. Phosphate buffer (v/v) was used as an aqueous solvent (A) and CH3CN as an organic solvent (B) in HPLC. Gradient elution of the analytes occurred at a flow rate of 1 milliliter per minute. Software generated chromatograms. Operating temperature of the HPLC instrument was room temperature (23 ± 2°C). After injecting 20 μl of each diluted extract into the HPLC three times, the average peak areas were produced and utilized for quantification. Based on the HPLC analysis, the chloroform leaf extract of Kalanchoe pinnata contained the following bioactive constituents: quercetin, gallic acid, and chlorogenic acid. Additionally, the presence of vitamins B1 and B3 was also noted. The different bioactive constituents eluted at different retention times, and their respective amounts were also detected.